Endo‐lysosomal protein concentrations in CSF from patients with frontotemporal dementia caused by CHMP2B mutation. Issue 1 (16th February 2023) - Toft, Anders; Sjödin, Simon; Simonsen, Anja Hviid; Ejlerskov, Patrick; Roos, Peter; Musaeus, Christian Sandøe; Henriksen, Emil Elbæk; Nielsen, Troels Tolstrup; Brinkmalm, Ann; Blennow, Kaj; Zetterberg, Henrik; Nielsen, Jørgen Erik
Abstract: Introduction: Increasing evidence implicates proteostatic dysfunction as an early event in the development of frontotemporal dementia (FTD). This study aimed to explore potential cerebrospinal fluid (CSF) biomarkers associated with the proteolytic systems in genetic FTD caused by CHMP2B mutation. Methods: Combining solid‐phase extraction and parallel reaction monitoring mass spectrometry, a panel of 47 peptides derived from 20 proteins was analyzed in CSF from 31 members of the Danish CHMP2B ‐FTD family. Results: Compared with family controls, mutation carriers had significantly higher levels of complement C9, lysozyme and transcobalamin II, and lower levels of ubiquitin, cathepsin B, and amyloid precursor protein. Discussion: Lower CSF ubiquitin concentrations in CHMP2B mutation carriers indicate that ubiquitin levels relate to the specific disease pathology, rather than all‐cause neurodegeneration. Increased lysozyme and complement proteins may indicate innate immune activation. Altered levels of amyloid precursor protein and cathepsins have previously been associated with impaired lysosomal proteolysis in FTD. Highlights: CSF markers of proteostasis were explored in CHMP2B ‐mediated frontotemporal dementia (FTD). 31 members of the Danish CHMP2B ‐FTD family were included. We used solid‐phase extraction and parallel reaction monitoring mass spectrometry. Six protein levels were significantly altered in CHMP2B ‐FTD compared with controls. Lower CSF ubiquitin levels in patients suggest association with disease mechanisms.